Investigation of the Strength of Textile Bonded Seams - Živilė JAKUBČIONIENĖ; Vitalija MASTEIKAITĖ; Tadas KLEVECKAS; Mindaugas JAKUBČIONIS; Urzamal KELESOVA (Medžiagotyra, 2012)
The strength of the textile bonded seams was analyzed. Two or more fabric layers joining are based on use of base layers structural properties and thermoplastic properties of adhesive film used for bonding. Five commercial produced fabrics of different structure (woven, knitted, laminate) and fiber content (polyester, cotton, flax) were used in this experiment. Thermoplastic polyurethane film was transferred from the base of silicone to fabric using 160 °C temperature and 10 seconds pressing duration. Fabric layers were bonded using 180 °C temperature and 30 seconds pressing duration. The strength of textile bonded seams was investigated using four different bond types, in order to determine method suitable for the analyzes of bonded seams of knitted fabrics and method suitable to analyze woven fabrics. DOI: http://dx.doi.org/10.5755/j01.ms.18.2.1922